LIBYA'S REVENUE FROM PETROLEUM - O'Brien, William (Dirasat in Economics and Business, 1968)
Today nearly everyone is aware that Libya is receiving substantial revenues from oil. However, the actual amounts, the revenue growth rate, the payments per barrel of oil and the manner in which company payments to the Government are calculated are not so widely known. In this paper I shall try to clarify these aspects of Libya's revenue from petroleum.